Contemporary drug synthesis (Wiley-Interscience, 2004)
The pharmaceutical industry is unquestionably vibrant today, with drug synthesis making a vital contribution. Whether in the early developmental stages of identifying and optimizing a lead, or the latter stages of process development and cost-effective scale-up, the ability to design elegant and economical synthetic routes is often a major factor in the eventual viability and commercial success of a drug.